DAMPAK TEKNOLOGI DIGITAL TERHADAP PERILAKU BELAJAR SISWA DI SD NEGERI 2 KESIMAN - A.A.Istri Mirah Dharmadewi; Anak Agung Ayu Ary Susanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to analyze in depth how the use of digital technology affects student learning behavior at SD Negeri 2 Kesiman in the context of 21st-century learning. This study uses a qualitative descriptive method by synthesizing various previous research findings on digital-based learning in elementary schools. The analysis results show that digital technology has several positive impacts, including increasing student access to more diverse learning resources, strengthening learning motivation through interactive media, and encouraging active student participation through the use of learning applications, educational videos, and other digital platforms. Furthermore, digital technology can enrich the learning experience through collaborative activities and more creative problem-solving. However, this study also found several negative impacts that need to be anticipated, such as decreased concentration due to distractions from non-educational content, increased dependence on devices, and reduced discipline and ability to manage learning time. These risks have the potential to hinder students' social-emotional development if technology use is not properly guided. Therefore, this study emphasizes the importance of teachers and parents in providing guidance, supervision, and fostering healthy technology use so that the benefits of digital technology can be maximized and its negative impacts can be minimized in the student learning process.